Myocardial Rupture following Carbon Monoxide Poisoning - Gabija Dragelytė; Jūris Plenta; Sigitas Chmieliauskas; Algimantas Jasulaitis; Romas Raudys; Tomas Jovaiša; Robertas Badaras (Case Reports in Critical Care)
We present the first case of severe cardiotoxicity of carbon monoxide leading to myocardial rupture and fatal outcome. 83-year-old woman was hospitalized 4 hours after the fire in her house with no respiratory or cardiac symptoms. After two days, she has suffered sudden collapse leading to cardiac arrest. Postmortem examination revealed intramural haemorrhage with myocardial rupture at the apex of the left ventricle. Minimal stenosis was noted in the proximal coronary arteries with no evidence of distal occlusion or any other long-standing heart disease. This case supports recommendations for targeted cardiovascular investigations in cases of CO poisoning.